Meu software: aplicativo para instruir o pedido de registro de programa de computador no Instituto Nacional da Propriedade Industrial - INPI - Pinho, José Alailson Sousa (2023)
The world revolves around information technology, and contemporary society is becoming increasingly technological. In this direction, software has become a fundamental piece for the technological revolutions of society and an indispensable element for the global economy. Thus, many technologies emerge in a short period of time, and the technological world revolves around two essential elements: software and hardware. The present study aimed to develop a free mobile application with centralized content for registering computer programs at the National Institute of Industrial Property - INPI. The methodology consisted of a qualitative and descriptive study, adopting bibliographic research to provide theoretical basis on the topic, and experimental research through the development of the application, in which usability data are analyzed. The application was developed using the Dart programming language and the Flutter Framework, and was evaluated by five experts, including three professionals in the software development field and two who work in the field of intellectual property. The result of this work is the application titled "Meu Software" (My Software), which is an application for Android devices, available for free on the Google Play Store. The application aims to contribute to the dissemination of knowledge about the registration of computer programs in Brazil, providing detailed information about the procedures and necessary steps in the registration process with INPI.